2021
DOI: 10.1049/itr2.12139
|View full text |Cite
|
Sign up to set email alerts
|

CT2‐MDS: Cooperative trust‐aware tolerant misbehaviour detection system for connected and automated vehicles

Abstract: Connected and automated vehicles (CAVs) are recognized as a promising solution to improve road safety. Before deploying CAVs, securing the communication environment is a critical challenge. To secure the exchanged sensitive messages between CAVs, a novel cooperative trust-aware tolerant misbehaviour detection system (CT2-MDS) is proposed in this paper. The vehicle-to-everything (V2X) network model in real complex scenarios is built first, and several typical types of attacks are simulated. The cooperative trus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Liu et al 81 suggested a new cooperative trust‐aware tolerant misbehavior detection system (CT2‐MDS) to protect the transmitted sensitive communications between connected and automated vehicles. First, a network model for the V2X system is constructed, and various common forms of assaults are simulated.…”
Section: Technical Analysis Of Connectivity In Vanetsmentioning
confidence: 99%
“…Liu et al 81 suggested a new cooperative trust‐aware tolerant misbehavior detection system (CT2‐MDS) to protect the transmitted sensitive communications between connected and automated vehicles. First, a network model for the V2X system is constructed, and various common forms of assaults are simulated.…”
Section: Technical Analysis Of Connectivity In Vanetsmentioning
confidence: 99%
“…The authors evaluated the proposed approach using a real-world vehicular network traffic dataset and compared it to traditional anomaly detection methods. The authors of [23] proposed a cooperative trust-aware tolerant misbehavior detection system (CT2-MDS) to detect misbehavior in a cooperative environment. They used trust management and machine learning techniques to detect misbehavior.…”
Section: Related Workmentioning
confidence: 99%
“…They pointed out that there is a lack of uniform evaluation metrics for performance measurements and that the trade-off between computational complexity and detection efficiency should be properly leveraged. Since a single machine learning method often has limitations while dealing with multiclass classification problems, Liu et al [23] combined several classifiers through a tree structure to improve classification accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Since a single machine learning method often has limitations while dealing with multi‐class classification problems, Liu et al. [23] combined several classifiers through a tree structure to improve classification accuracy.…”
Section: Introductionmentioning
confidence: 99%